Developing a light rail project delegate information : Friday 20 October 1995, to be held at the Novotel Hotel, Sheffield. (Thomas Telford, 1995)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a conference held at Novotel Hotel, Sheffield on 20 October 1995.
Keywords: Railroads, Local and light -- Design and construction -- Congresses.; elektronické knihy; electronic books